The Emergence of Skills in Moroccan Higher Education: A Qualitative Study on Stakeholders’ Attitudes, Views and Expectation - Birrou, Zineb; Kich, Aziz; Larouz, Mohamed (Andalas International Journal of Socio-Humanities, 2021)
This paper provides an exploration of a range of perspectives and attitudes towards the emergence of Life Skills in the Moroccan Higher Education curricula. We briefly introduce the national context of the Bachelor’s Degree Reform (BDR) of 2019 introducing these skills as well as the international proactive measures to create a new space for well-being policies and assessments.  The focus of the present article is to explore the students and professors’ views on officially integrating such innovative modules within the academic program for the first time. In order to obtain relevant data, a qualitative approach was adopted. The findings suggest that the majority of interviewed university professors were supportive of the aforementioned reform (BDR). The reluctant minority voiced out their concerns over the lack of clarity regarding the teaching and evaluation methodologies for skills in which there has been no proper teacher training yet. On the other hand, the students’ narratives after a six-week experimental Life Skills-based course suggest that the intervention was very successful, and seems to enhance emotional, and psychological health, therefore cultivating their overall Well-being and resilience. In other words, their attitudes were unanimously positive and their perceived impact of the course deeply transformational.